2018
DOI: 10.1111/os.12414
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Induce Apoptosis of Giant Cells Tumor of Bone via TP53INP1 Signaling

Abstract: Objective To evaluate the antitumor capability and to investigate the underlying molecular mechanism of paclitaxel. Methods First, cck‐8 and apoptosis assays were used to determine survival and apoptotic effects of HS 737.T cells under treatment of paclitaxel. Next, RNA‐seq and bioinformatics were used to determine the differentially expressed genes and to analyze the pathway involved. Quantitative real‐time polymerase chain reaction was used to verify the accuracy of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The RT-PCR analysis further confirmed that CXCL8 was downregulated significantly upon the Siglec-15 knockdown ( Figure 8 E). Many studies have indicated that the CXCL family plays critical roles in the regulation of cancer development [ 29 , 30 , 31 ]. To identify the downstream genes linked to CXCL8, we found the nine highest-linked candidate genes (CXCL2, CXCL3, CXCL5, CXCL10, CXCL11, ADORA1, BDKRB1, C5AR1, and NMU) in module 2 ( Figure 8 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RT-PCR analysis further confirmed that CXCL8 was downregulated significantly upon the Siglec-15 knockdown ( Figure 8 E). Many studies have indicated that the CXCL family plays critical roles in the regulation of cancer development [ 29 , 30 , 31 ]. To identify the downstream genes linked to CXCL8, we found the nine highest-linked candidate genes (CXCL2, CXCL3, CXCL5, CXCL10, CXCL11, ADORA1, BDKRB1, C5AR1, and NMU) in module 2 ( Figure 8 D).…”
Section: Resultsmentioning
confidence: 99%
“…The human GCTB stromal cells (Hs737. T) were purchased from the American Type Culture Collection (ATCC) and were then cultured in a high-glucose DMEM, containing 15% FBS and 1% penicillin/streptomycin, at 37 °C in a humidified 5% CO 2 atmosphere [ 29 ]. When the GCTB stromal cell confluence reached 80–90%, the cells were digested by 0.25% trypsin-EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Our study found that miR-205-5p and TP53INP1 were involved in curcumin-mediated effects on the biological functions of C6661-IR, and the former directly targeted the latter. TP53INP1 is located on the human chromosome 8q22 and plays a vital role in the apoptotic network [41]. It can be activated by p53, p73, and E2F, leading to apoptosis and cell cycle arrest [42].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is widely accepted as a process of programmed cell death. Studies have shown that PTX and its agent can induce apoptosis of tumor cells, such as giant cells, sarcoma cells, lung cancer cells, breast cancer cells, and liver cancer cells ( Ren et al, 2018 ; Xiao et al, 2019 ; Li et al, 2020 ; Xiaomeng et al, 2020 ). Therefore, we investigated whether PTX induces FLS apoptosis.…”
Section: Discussionmentioning
confidence: 99%